The design of thermal management system for hypersonic launch vehicles based on active cooling networks. (August 2019) - Gou, Jian-Jun; Chang, Yue; Yan, Zheng-Wei; Chen, Bing; Gong, Chun-Lin
Highlights: A TMS consisting of passive TPS and ACN is developed for a hypersonic launch vehicle. The coupled design method of TPS and ACN is developed based on an equivalent thermal equilibrium model. An equivalent HTC is proposed to indicate the overall capacity of ACN. Abstract: In this paper, a design method of thermal management system (TMS) for hypersonic vehicles is developed. The system consists of a passive thermal protection system (TPS) and an active cooling network (ACN) with coolant of kerosene. In most previous studies, the passive TPS and ACN are always designed separately and thus leads to over-conservative results that deviating from real engineering conditions. A coupled design method is developed in present work, and the process includes calculation of aerodynamic heat, determination of passive TPS concept distribution, computation of TPS and ACN scales, and iterative design. The coupled design is realized based on two keys, the active cooling is coupled in aerodynamic heating and heat transfer in TPS by an equivalent thermal equilibrium model, and the overall capacity of active cooling is indicated by an equivalent heat transfer coefficient. The model and the coefficient act as the rationale and the equivalent parameter of the whole process, respectively. The TMS of a reusable launch vehicle is established under a typical trajectory. The influences of equivalent heat transfer coefficient on aerodynamic heating, passive TPS and ACN are studied. The results show that the weight of passive TPS decreases, while the coolant mass flow rate increases with the enhancement of active cooling.